Immunohistochemical Study of TGF-β1 in Oral Leukoplakia and Oral Squamous Cell Carcinoma: Correlations Between Clinicopathologic Factors and Overall Survival. Issue 9 (October 2017) - Wagner, Vivian P.; Cardoso, Paula R.; dos Santos, Jean N.; Meurer, Luise; Vargas, Pablo A.; Fonseca, Felipe P.; Carrard, Vinicius C.; Martins, Manoela D.
Abstract : The aim of the present study was to analyze transforming growth factor β1 (TGF-β1) expression in cases of leukoplakia and oral squamous cell carcinoma (OSCC) and to correlate these expression profiles with proliferative labeling index, clinicopathologic factors, and clinical outcome. Clinical data for 24 cases of leukoplakia and 87 cases of OSCC were retrieved from medical records. OSCC tissues were included into tissue microarray blocks and sections of normal mucosa, leukoplakia, and OSCC tissue microarray's were prepared on slides. Immunohistochemistry was used to detect expression of TGF-β1 and Ki67. The expression of TGF-β1 and Ki67 were significantly increased from normal mucosa, through leukoplakia to OSCC. High expression of TGF-β1 correlated with an increase in proliferative labeling index. No association between TGF-β1 expression and the clinicopathologic factors examined was observed. Expression of TGF-β1 also did not associate with clinical outcome in either of groups. Our results suggest that changes in TGF-β1 are associated with the progression of oral carcinogenesis.